The Influence of Brand Strength on Word Of Mouth Through Customer Satisfaction and Customer Loyalty on General Achmad Yani University Students - Abdul Ahmad Hafidh Nurmansyah; Khaerul Rizal Abdurahman (International Journal of Science and Society, 2022)
Colleges must carry out several market strategies to compete. One of these strategies is to increase brand strength to improve marketing performance. This study aimed to analyze the impact of brand strength on customer satisfaction, customer loyalty, and WOM. The analysis method uses a quantitative approach with Structural Equation Modeling (SEM). This study involved a sample of the Unjani student population. The minimum number of samples in research using multivariate analysis methods, including multiple regression, is 10 times the number of variables. The research model and research hypotheses were tested using Structural Equation Modeling. For positive mediated Word of Mouth (WOM), the results showed that there was no significant positive effect of Brand Familiarity mediated by Customer Loyalty on positive mediated Word of Mouth (WOM); There is no significant positive effect of Brand Remarkability mediated by Customer Loyalty on positive mediated Word of Mouth (WOM). Finally, Customer Satisfaction influences positive Word of Mouth (WOM) via Customer Loyalty.